2009
DOI: 10.1080/14653240902807034
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-grade ex vivo-expanded human natural killer cells up-regulate activating receptors and death receptor ligands and have enhanced cytolytic activity against tumor cells

Abstract: Background-Cancer immunotherapy involving NK-cell infusions and administration of therapeutic agents modulating the susceptibility of tumors to NK-cell lysis has been recently proposed. Here we provide a method to expand highly cytotoxic clinical grade NK cells in vitro for adoptive transfer following bortezomib treatment in patients with advanced malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
241
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(257 citation statements)
references
References 26 publications
4
241
1
6
Order By: Relevance
“…21-23 D.A. Lee and co-workers have developed a method for large-scale production of highly potent NK cells using K562 cells engineered to express 4-1BB ligand and membrane bound IL21 (mb21).…”
Section: Introductionmentioning
confidence: 99%
“…21-23 D.A. Lee and co-workers have developed a method for large-scale production of highly potent NK cells using K562 cells engineered to express 4-1BB ligand and membrane bound IL21 (mb21).…”
Section: Introductionmentioning
confidence: 99%
“…The safety and antitumor effects of autologous NK cells expanded from PBMCs were investigated in a phase I trial in patients with advanced metastatic tumors and hematological malignancies. 164 Large-scale ex vivo alloreactive NK cell expansion suitable for multiple donor lymphocyte infusions in AML was reported. This protocol involved that NK cells purified by CliniMACS were cultured in closed air-permeable culture bags with certified culture medium and other components, including human serum, IL-2, IL-15, anti-CD3 antibody and autologous irradiated feeder cells.…”
Section: Expanding Nk Cells For Clinical Practicementioning
confidence: 99%
“…As summarized in Table 2, Epstein-Barr virustransformed lymphoblastoid cell lines, genetically modified K562 cells, or irradiated autologous cells were used as feeder cells to promote NK cell expansion from PBMCs. [164][165][166][167] The Campana group has developed a master cell bank of K562 feeder cells expressing a membrane-bound form of IL-15 (mbIL15) and 4-1BB ligand (K562-mb15-41BBL) under cGMP guidelines, and demonstrated that large-scale expansion and activation of human NK cells for clinical studies was feasible. 165 These NK cells demonstrated cytotoxic activity toward tumor cells even higher than observed in the initial small-scale experiments.…”
Section: Expanding Nk Cells For Clinical Practicementioning
confidence: 99%
“…[11][12][13][14] To overcome these limitations, several methods have been explored to activate and expand NK cells before adoptive transfer. [15][16][17][18][19][20] Alternatively, NK cells can be generated from hematopoietic progenitor cells (HPCs). [21][22][23][24][25] Previously, we reported a good manufacturing practice (GMP)-compliant, cytokine-based culture protocol for the ex vivo generation of allogeneic NK cells from CD34 C HPCs isolated from cryopreserved umbilical cord blood (UCB) units, bone marrow (BM), or G-CSF-mobilized blood (see ref.…”
Section: Introductionmentioning
confidence: 99%